2022
DOI: 10.1007/s11886-022-01799-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitor, Insulin Pump, and Automated Insulin Delivery Therapies for Type 1 Diabetes: An Update on Potential for Cardiovascular Benefits

Abstract: Purpose of Review The incidence of type 1 diabetes (T1D) is rising in all age groups. T1D is associated with chronic microvascular and macrovascular complications but improving glycemic trends can delay the onset and slow the progression of these complications. Utilization of technological devices for diabetes management, such as continuous glucose monitors (CGM) and insulin pumps, is increasing, and these devices are associated with improvements in glycemic trends. Thus, device use may be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 143 publications
0
15
0
2
Order By: Relevance
“… 30 Meanwhile, a higher glucose fluctuation was more likely to occur among type 1 diabetes because of the absolute insulin deficiency and inappropriate use of hypoglycemic drugs. 31 , 32 Moreover, Shen et al 4 also highlighted that hypoglycemia played a significant mediating role between HbA1c variability and the incidence of CVD. Similarly, our subgroup analysis for per HbA1c‐SD showed that the risk of CVD was significantly higher among patients with type 1 diabetes than those with type 2 diabetes, which might be attributed to a vulnerably worse glycemia control, a high incidence of hypoglycemia, and the functional loss of islet cells among type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Meanwhile, a higher glucose fluctuation was more likely to occur among type 1 diabetes because of the absolute insulin deficiency and inappropriate use of hypoglycemic drugs. 31 , 32 Moreover, Shen et al 4 also highlighted that hypoglycemia played a significant mediating role between HbA1c variability and the incidence of CVD. Similarly, our subgroup analysis for per HbA1c‐SD showed that the risk of CVD was significantly higher among patients with type 1 diabetes than those with type 2 diabetes, which might be attributed to a vulnerably worse glycemia control, a high incidence of hypoglycemia, and the functional loss of islet cells among type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that hypoglycemia might not be effectively controlled for patients with type 1 diabetes, which facilitated worse glycemia control, ultimately leading to an increased risk of CVD 30 . Meanwhile, a higher glucose fluctuation was more likely to occur among type 1 diabetes because of the absolute insulin deficiency and inappropriate use of hypoglycemic drugs 31,32 . Moreover, Shen et al 4 also highlighted that hypoglycemia played a significant mediating role between HbA1c variability and the incidence of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the diabetes patients were equipped with an insulin pump and/or had an FSL device for continuous glucose monitoring. Thanks to advances in glycemic control methods, these types of equipment improve glycemic management and are associated with a decrease in systemic vascular complications [ 26 , 27 , 30 ]. Interestingly, our investigation found that continuous glucose monitoring using devices such as the FSL was associated with higher retinal vascular densities in the SCP and DCP.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a comparative study investigating continuous subcutaneous insulin infusion (CSII) versus multiple daily injections (MDI) demonstrated positive results, indicating improved lifestyle flexibility and reduced stress related to hypoglycemia among CSII users [7] . Moreover, leading endorsements from reputable bodies such as American Diabetes Association (ADA) and International Society for Pediatric and Adolescent Diabetes (ISPAD) support the consideration of insulin pump therapy because of its proven safety and effectiveness [8] .…”
mentioning
confidence: 99%
“…The satisfaction experienced by users can be attributed to a range of factors, including the meticulous design of the devices, the accuracy of the data provided, and the reduction in nocturnal alarm disruptions. This culmination of positive elements leads to better diabetesrelated outcomes and a notable reduction in stress levels [12,13] .…”
mentioning
confidence: 99%